Systematic Reviews on Teacher Identity in Brazilian Journals: : Advances and Limits - Diniz Lira, André Augusto (2024)
This article examines a series of systematic reviews on teacher identity published in Portuguese in Brazilian journals from the 2000s onwards, using their theoretical-methodological aspects and primary research focuses as the central points of discussion. A search was conducted on the Capes Periodicals Portal, the Carlos Chagas Foundation's Educ@ Platform and SciELO Brazil, as well as in researchers' personal collections, resulting in twelve studies. The reviewed articles address various aspects of teaching identity, encompassing broader themes and specific domains (mathematics education, physical education, biology and medicine) especially since the mid-2000s, in alignment with international trends. Finally, the article highlights the advancements and limitations of these studies.